„Nie jesteś za młody, żeby zmieniać świat” – studium przypadku zjawiska dziecięcego aktywizmu klimatycznego - Małgorzata Kowalik-Olubińska (Problemy Wczesnej Edukacji)
A social movement, which unites people around the idea of caring about the future of the Earth, climate and intergenerational justice is called climate activism. It has been on the rise due to the involvement of an increasing number of children and the youth. The aim of the study was to carry out an in-depth review of the phenomenon of children’s climate activism. The collective case study served as the main method. 15 cases of young climate activists from all around the world were analysed. The study sample consisted of young activists aged 7–12. The study revealed that the fight for a better tomorrow for all people and the whole planet is the essential conviction, which lies behind actions of young climate activists. By becoming public actors they demand appropriate actions to be taken by adults. The voice of children can be heard through petitions, open letters, campaigns, protests and speeches. Children’s climate activism is a form of children’s disagreement towards the passiveness of adults in the light of the growing environmental crisis. The causative power of children is seen as a phenomenon emerging from the network of relations established between various social actors.